1965
DOI: 10.1097/00002060-196512000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Tonus in Postural Muscles

Abstract: The author wishes t o express his appreciation to Mr. Barrett B. Weeltes for technical assistance. 275(1) 200 cps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

1970
1970
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
2
1
Order By: Relevance
“…In contrast, lower gap values were observed in lower limb musculature for both the discrete task and daily activity. Weight-bearing locomotor activities are key contributors to total body energy expenditure for sedentary lifestyles [28], whereas sitting and quiet standing do not effectively activate the hamstring or vastus muscles [29,30]. Subjects in the present study reported mobility levels (moving, standing, stairs), that were generally higher than sedentary scores, suggesting the discrepancy between our findings and prior studies [13,27] was due to more active subjects in the present study.…”
Section: Muscle-related Differencescontrasting
confidence: 95%
“…In contrast, lower gap values were observed in lower limb musculature for both the discrete task and daily activity. Weight-bearing locomotor activities are key contributors to total body energy expenditure for sedentary lifestyles [28], whereas sitting and quiet standing do not effectively activate the hamstring or vastus muscles [29,30]. Subjects in the present study reported mobility levels (moving, standing, stairs), that were generally higher than sedentary scores, suggesting the discrepancy between our findings and prior studies [13,27] was due to more active subjects in the present study.…”
Section: Muscle-related Differencescontrasting
confidence: 95%
“…force produced) to incrementally increasing electrical stimulations (Lucas 1905, Eccles and Sherrington 1930, Rosenblueth et al 1941, Loofbourrow 1948, while later studies recorded the electrical output (i.e. EMG) of the muscle during incremental voluntary contractions (Inman et al 1952, Lippold 1952, de Vries 1965. The relationship between skeletal muscle electrical activity and force has been shown to be highly linear and positive (Lippold 1952, de Vries 1965, de Vries 1968, Milner-Brown and Stein 1975, Moritani and de Vries 1978.…”
Section: Importance Of the Emg Amplitude Versus Force Relationshipmentioning
confidence: 99%
“…EMG) of the muscle during incremental voluntary contractions (Inman et al 1952, Lippold 1952, de Vries 1965. The relationship between skeletal muscle electrical activity and force has been shown to be highly linear and positive (Lippold 1952, de Vries 1965, de Vries 1968, Milner-Brown and Stein 1975, Moritani and de Vries 1978. Multiple studies have suggested that decreases in the linear slope coefficient (a measure of the efficiency of electrical activity) between EMG amplitude and force may be indicative of increases in skeletal muscle mass (Fischer and Merhautova 1961, de Vries 1968, Moritani and de Vries 1979.…”
Section: Importance Of the Emg Amplitude Versus Force Relationshipmentioning
confidence: 99%